2015
DOI: 10.1002/nbm.3321
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of GABA+ in migraine detected using 1H‐MRS

Abstract: γ-Aminobutyric acid (GABA) has been implicated in several pain conditions, yet no study has systematically evaluated GABA levels in migraine using (1) H-MRS. The accurate detection, separation and quantification of GABA in individuals with migraine could elucidate the role of this neurotransmitter in migraine pathophysiology. Such information may eventually be useful in the diagnosis and development of more effective treatments for migraine. The aims of this study were therefore to compare the concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 31 publications
0
47
1
Order By: Relevance
“…The implication of GABA in the pathogenesis of migraine is supported by several biochemical, pharmacological, neurophysiological, and experimental data, that are summarized in the Table (data included in this table were selected from those obtained through a PubMed Search crossing the terms “migraine” with “GABA” or “gamma‐aminobutyric acid” from 1966 to March 15, 2017, that retrieved a total of 271 references).…”
Section: Biochemical Pharmacological Neurophysiological and Experimentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of GABA in the pathogenesis of migraine is supported by several biochemical, pharmacological, neurophysiological, and experimental data, that are summarized in the Table (data included in this table were selected from those obtained through a PubMed Search crossing the terms “migraine” with “GABA” or “gamma‐aminobutyric acid” from 1966 to March 15, 2017, that retrieved a total of 271 references).…”
Section: Biochemical Pharmacological Neurophysiological and Experimentioning
confidence: 99%
“…Russo et al 43 identified a susceptibility locus for familial migraine 5 out of 10 families (25 affected members) with MWA in the 15q11-q13 genomic region which cointained the GABRB3, GABRA5, and GABRG3 genes, with the higher linkage for markers of the GABRA5 gene (LOD score of 6.54 using multipoint linkage analysis), but two extensive case-control association studies involving, respectively, 649 patients with MWA and 652 controls (analyzing 17 tagging SNPs for GABRB3, 4 for GABRA5, and 30 for GABRG3), 44 898 patients with MWA and 900 controls (analyzing 19 tagging SNPs for GABRB3, 6 for GABRA5, and 5 for GABRG3), 45 failed to show association between SNPs in these genes and the risk for migraine. Brain GABA Levels Aguila et al, using single-voxel proton magnetic resonance spectroscopy ( 1 HMRS) with the voxel positioned lateral to the midline posterior cingulate, and posterior and superior to the splenium of the corpus callosum), found significantly higher brain GABA levels in 19 migraine patients than in 19 age-and gender-matched control subjects, 8 and described positive association between GABA levels and pain and central sensitization scores. 9 Bridge et al 10 reported decreased GABA levels in the occipital cortex of 13 females with migraine with visual aura patients when compared with 13 female controls.…”
mentioning
confidence: 99%
“…In the episodic form of migraine, headache occurs on average on less than 15 days per month, whereas in the chronic form (CM), headache occurs on ≥15/days per month for at least three consecutive months. 6 Pain sensation related to migraine is produced by multidirectional and parallel processing cascades between relay stations located in the brainstem (trigeminal nucleus caudalis) and the brain. MwA affects about 20-30% of migraine patients.…”
Section: Introductionmentioning
confidence: 99%
“…While increases in Glx are corresponded to increased pain perception, GABA[44,58,59] is an inhibitory neurotransmitter which plays an important role with Glx in neurotransmission and pain. GABA concentration in brain tissue in vivo is relatively low (< 2 mmol/L), and the MRS spectrum shows strong overlap with other metabolites.…”
Section: Clinical Applications Of Mrs and Future Directionsmentioning
confidence: 99%